GAMBARAN KEMAMPUAN FUNGSIONAL NECK TERHADAP DURASI KERJA PEGAWAI YANG MENGALAMI NECK PAIN - Al Gifari, Muhammad Yusrin; Permatasari, Dian Intan; Arial, Nurintan Purnamasari (Politeknik Unggulan Kalimantan, 2023)
Neck Pain is pain related to posture, sleeping habits, work position, stress, chronic muscle fatigue, degenerative changes of the cervical disc. Purpose: The aim of this research is to find out about the description of the functional ability of the neck on the duration of work of the Politeknik Unggulan Kalimantan employees who experience neck pain. Method: Type of quantitative research with a descriptive analytic research design. This method is used to determine the value of the functional ability of the neck of the employees of the Politeknik Unggulan Kalimantan who experience neck pain by using the Neck Disability Index (NDI). Results: The results of the research conducted showed that the most experienced neck pain was 37 employees with a percentage of 94.5%, based on the duration of the employee's work more duration of 8 hours of work with a percentage of 97%, impaired functional ability of the neck in Polish employees who experience neck pain a maximum of 24 employees with a presentation of 65%. Conclusion: The incidence of neck pain was found among the employees of the Politeknik Unggulan Kalimantan.